2018
DOI: 10.1016/j.physletb.2018.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tensor forces in nuclear spin–orbit splittings from ab initio calculations

Abstract: A systematic and specific pattern due to the effects of the tensor forces is found in the evolution of spin-orbit splittings in neutron drops. This result is obtained from relativistic Brueckner-Hartree-Fock theory using the bare nucleon-nucleon interaction. It forms an important guide for future microscopic derivations of relativistic and nonrelativistic nuclear energy density functionals.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 94 publications
(121 reference statements)
8
69
0
Order By: Relevance
“…As shown in Ref. [233], the evolution of SO splittings in neutron drops gives a clear hint of the tensor force in the nuclear density functional, which has been the topic of long debates in the past [130].…”
Section: Spin-orbit Splitting and Tensor Effectsmentioning
confidence: 88%
See 1 more Smart Citation
“…As shown in Ref. [233], the evolution of SO splittings in neutron drops gives a clear hint of the tensor force in the nuclear density functional, which has been the topic of long debates in the past [130].…”
Section: Spin-orbit Splitting and Tensor Effectsmentioning
confidence: 88%
“…Without further specification, all the results of neutron drops shown below are calculated in an external harmonic oscillator field Figure 17 shows the total energy divided by ωN 4/3 for N-neutron drops (N from 4 to 50 for Bonn A and from 4 to 28 for Bonn B and C) in a HO trap ( ω = 10 MeV) calculated by RBHF theory [233,234]. The factor ωN 4/3 is based on the consideration that, in the Thomas-Fermi approximation [145], the total energy for a non-interacting N-fermion system in a HO trap is given by…”
Section: General Propertiesmentioning
confidence: 99%
“…In this case we hope to be able to gain a parameter-free, microscopic understanding of open questions in modern phenomenological density functional theories, such as their isospin dependence or the importance of the tensor terms. As an example it has been found that the spin-orbit splitting in neutron droplets shows a very characteristic behavior as a function of the neutron number, which can be reproduced in phenomenological functionals with tensor terms of an appropriate size [29].…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned in Ref. [50], the evolution of the spinorbit splittings by RBHF theory can be used to constrain the tensor force. On the other hand, the spin-orbit splittings given by RBHF theory using Bonn A interaction are slightly smaller than experimental data [39,40].…”
Section: Numerical Detailsmentioning
confidence: 99%